New understanding and exploration direction of hydrocarbon accumulation in Termit Basin, Niger - Shengqiang YUAN; Lirong DOU; Dingsheng CHENG; Fengjun MAO; Chunfu PAN; Fengyun ZHENG; Hong JIANG; Wenzhu PANG; Zaohong LI (Petroleum Exploration and Development, 2023)
Based on the seismic and drilling data, casting thin sections, geochemical analysis of oil and rock samples, and hydrocarbon generation history simulation, the hydrocarbon accumulation characteristics and exploration direction of Termit superimposed marine—continental rift basin are discussed. The Termit basin is superimposed with two-phase rifts (Early Cretaceous and Paleogene). The subsidence curves from two wells on the Trakes slope in the east of the basin show high subsidence rate in the Late Cretaceous, which is believed to be high deposition rate influenced by transgression. However, a weak rift may also be developed. The depositional sequences in the Termit basin were controlled by the Late Cretaceous marine transgression cycle and the Paleogene lacustrine transgression cycle, giving rise to two types of superimposed marine—continental “source-sink” deposits. The marine and continental mixed source rocks developed universally in the whole basinduring the marine transgression period, and are overlaid by the Paleogene Sokor 1 reservoir rocks and Sokor 2 caprocks developed during the lacustrine transgression period, forming the unique superimposed marine—continental basin in WCARS. The early low geothermal gradient in the Termit basin resulted in the late hydrocarbon generated by the source rock of Upper Cretaceous Yogou in Paleogene. Mature source rock of Upper Cretaceous Donga developed in the Trakes slope, so that the double-source-supply hydrocarbon and accumulation models are proposed for the Trakes slope in which formed the oil fields. Due to virtue of the newly proposed hydrocarbon accumulation model and the exploration activities in recent years in the Termit superimposed marine—continental rift basin, an additional effective exploration area of about 2500 km2 has been confirmed in the east of the basin. It is believed that potential domains such as Sokor 1, Donga and Upper Cretaceous lithologic traps in the southeast of the basin are key expected targets for exploration and frontier evaluation in future.